ESTIMASI LIMBAH INDUSTRI TAHU DAN KAJIAN PENERAPAN SISTEM PRODUKSI BERSIH - Sjafruddin, Rahmiah; Agustang, Andi; Pertiwi, Nurlita (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of this research is to determine the potential of solid and liquid waste produced from the tofu industry and do conduct management and processing studies by approach the clean production process applied to the tofu industry. Research methods were done through interviews and observations in the tofu industry in the urban village of Bara-Barayya. The results of the determination of the mass balance of the soybean washing and clumping with the each wastewater capacity range of 1,485 L and 1,262 L. The process of tofu production was totally producing solid waste of 420.65 kg per day and waste water ranged from 3,065.4 liters per day for production capacity of 150 kg of soybean or equivalent to 20.4 m3/ton daily. Predictions of waste water potential in the washing and clumping process in a month-on time was modeled using the Stella program. The quality standard of waste water for the soybean processing for the highest of 20 m3 per ton. Implementation of net production process were through the process of good house keeping, recycle, and on-site-reuse process.